PENGARUH CAPITAL ADEQUACY RATIO (CAR), NON PERFORMING LOAN (NPL), DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP RETURN ON ASSET (ROA) PADA BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2019 - Ni Putu Widya Ariyanti; I Wayan Sukadana; I Wayan Suarjana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2022)
ROA is one of the profitability ratios used to measure the performance of a bank or company by comparing profit before tax with total assets (assets) owned by the bank in a certain period. The greater the ROA value, the better the ability of banks to generate profits. This study aims to examine and obtain empirical evidence of the effect of CAR, NPL, and LDR on the ROA of commercial banks listed on the Indonesia Stock Exchange in 2017 – 2019. The research population is commercial banks listed on the Indonesia Stock Exchange in 2017 – 2019. The sample in this study was 15 commercial banks which were determined based on the method purposive sampling. The analytical technique used to test the hypothesis ismultiple linear regression analysis technique. The results show that CAR has a positive effect on ROA, NPL has a negative effect on ROA. While LDR has no effect on ROA. Further research can develop this research by using other variables that in theory have an influence on ROA, such as BOPO (Operating Costs/Operational Income).